Makna Sor Singgih Basa bagi Generasi Z: Studi Fenomenologi Komunikasi Interpersonal dalam Konteks Kasta di Bali - I Gusti Arya Agung Restu Diva Dewangga; Putri Ekaresty Haes; Kadek Adyatna Wedananta; Putu Suparna (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to explore Generation Z's adaptation to traditional values, particularly the Balinese language sor singgih in Catur Wangsa, amid social changes driven by globalization and technological advancements, from the perspective of interpersonal communication. The phenomenological approach in qualitative research is the research method used, with three data collection techniques: participant observation, unstructured interviews, and documentation. This study also uses source and technique triangulation as a data validity technique. The research informants are members of Generation Z from the five castes in Bali: Brahmana, Ksatria, Weisya, and Sudra. Research conducted across eight districts and cities in Bali indicates that Generation Z is beginning to shift its interpersonal communication patterns. Although they still uphold traditional values of politeness and social norms, Generation Z emphasizes equality and openness in their daily interactions. The generation Z that continues to use the Balinese language is segmented by social context, emotional closeness, and communication situations, rather than solely by caste differences. Furthermore, this study's findings show that the caste system is seen more as a cultural identity than a social boundary. The implications of this research emphasize the importance of preserving the values of Balinese local wisdom in the form of adaptive, egalitarian communication that is relevant to the development of the younger generation in the digital age.